A Simple Method for Implementation of a Solar Oven for Lumber Drying - Escudero-Villa, Pedro (2024)
In Ecuador, the small and medium-sized wood industries dedicated to the manufacture of boards use a form of natural drying, which takes six months to two years depending on the moisture content, the type of wood, and the thickness. In regular bases, the natural drying process requires six months to obtain dry wood that can be processed to final products, which causes delays in the delivery of production batches and loss of time, affecting the internal economy. In this work, we present a design for a simple implementation of a solar oven to dry wood and derivatives. For this objective, we included the oven chamber physical dimensioning, the requirements and thermodynamic analysis, and a comparison with the standard traditional method. The oven was dimensioned to keep a range of temperature from 15 to 45° in a chamber of . The result of this design allows a time saving of 66.67% and profits of 304% per month for a standard wood processed. These results are possible due to the specific geographical location and climate of Ecuador, which directly influence the effectiveness of a solar oven.